Optimalisasi Pembentukan Desa Anti Korupsi Desa Senduro Kabupaten Lumajang Jawa Timur - Suharnanik Suharnanik; Umar Sholahudin; Ratih Retnowati (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2023)
Anti-corruption village is a program that aims to create a village that is free from corruption. Community service was carried out in Senduro Lumajang Village, East Java Province. Senduro Village is a village with unique culture and traditions, such as Javanese customs and the unique customs of the Tengger Tribe. Senduro Village has attractive tourism potential, such as Tancak Waterfall, Banyu Anjlok Waterfall, and Coban Rondo Senduro Waterfall. The potential of the village provides a lot of income for Senduro village so the management of natural resource products must be monitored so that their utilization is for the welfare of the people and not for corruption. Therefore this community service aims to prevent acts of corruption within the Senduro village government and promote transparency, accountability, community participation, and integrity in financial management and public services. The results of this activity have an impact on increasing knowledge of corruption actions to become an anti-corruption village. In the future, it is suggested that more routine related pieces of training be carried out in maintaining an anti-corruption village because these activities have a significant impact on building an independent and integrated village.